KERALA Dubious Development Petrochemicals Complex at Cheemeni - K Ramachandran (Economic and Political Weekly January 10, 1998, 1998)
The proposal to set up a huge petrochemicals complex in a green, water-rich and fertile region of Kerala with tie-ups with several TNCs, is being rushed through with unseemly haste. Little information on the processes has been made available to the public nor has there been a proper scientific assessment of the potential environmental consequences of the plant